Prevalence of child maltreatment in a nationwide sample of 18 to 31 year-olds in Germany - Christoph Kasinger; Robert Schlack; Elmar Brähler; Jörg M. Fegert; Vera Clemens (BMC, 2024)
Abstract Background Child maltreatment (CM) can have devastating and potentially lifelong effects for those affected and is a major contributor to mental health problems. To tackle public health problems it is crucial to have reliable data on CM. The aim of this study is to assess the prevalence and predictors of CM in a nationwide sample of the German population of young adults. Methods The study population (young adults aged 18 to 31 years) stems from the KiGGS Cohort study, the longitudinal branch of the German Health Interview and Examination Survey for children and adolescents. This sample meets the criteria of the United Nations Sustainable Development Goals (SDG) indicator 16.2.3. The data was collected between 2014 and 2017. CM were assessed with the Childhood Trauma Questionnaire (CTQ) in. In addition, socio-demographic variables and other known risk factors for CM were assessed. A total of 6433 (47.8% female) participants were included in the analyses. Binary logistic regression analyses were used to investigate predictors of maltreatment subtypes. Ordinal regression was used to examine their association with experience of multiple forms of CM. Results Overall, 18.4% (f: 20.9%, m: 16.1%) of the participants reported having experienced at least one type of CM; 6.7% (f: 8.8%, m: 4.8%) reported experiences of emotional abuse, 3.7% (f: 3.9%, m: 3.5%) physical abuse, 3.5% (f: 5.3%, m: 1.7%) sexual abuse, 9.0% (f: 9.9%, m: 8.2%) emotional neglect and 8.6% (f: 8.5%, m: 8.7%) physical neglect. Gender, subjective social status, education and household dysfunction (e.g. living with an individual who is using substances) emerged as significant predictors for different types of CM. Additionally, all these factors were significant risk factors for experiencing cumulative CM. Conclusions CM is common in the German population, with almost one in five people experiencing at least one type of CM. The results reveal important risk factors for the occurrence of CM. In particular, people with lower social status and those who grew up in dysfunctional households are at higher risk of CM. Greater support for this vulnerable population may reduce the prevalence of CM.